Tuberculosis among older adults in Zambia: burden and characteristics among a neglected group - Jenna Coffman; Pascalina Chanda-Kapata; Ben J. Marais; Nathan Kapata; Alimuddin Zumla; Joel Negin (BMC, 2017)
Abstract Background The 2010 Global Burden of Disease estimates show that 57% of all TB deaths globally occurred among adults older than 50 years of age. Few studies document the TB burden among older adults in Southern Africa. We focused on adults older than 55 years to assess the relative TB burden and associated demographic factors. Methods A cross sectional nationally representative TB prevalence survey conducted of Zambian residents aged 15 years and above from 66 clusters across all the 10 provinces of Zambia. Evaluation included testing for TB as well as an in-depth questionnaire. We compared survey data for those aged 55 and older to those aged 15-54 years. Survey results were also compared with 2013 routinely collected programmatic notification data to generate future hypotheses regarding active and passive case finding. Results Among older adults with TB, 30/ 54 (55.6%) were male, 3/27 (11.1%) were HIV infected and 35/54 (64.8%) lived in rural areas. TB prevalence was higher in those aged ≥55 (0.7%) than in the 15-54 age group (0.5%). Males had higher rates of TB across both age groups with 0.7% (15-54) and 1.0% (≥55) compared with females 0.4% (15-54) and 0.6% (≥55). In rural areas, the prevalence of TB was significantly higher among older than younger adults (0.7% vs 0.3%), while the HIV infection rate was among TB patients was lower (11.1% vs 30.8%). The prevalence survey detected TB in 54/7484 (0.7%) of older adults compared to 3619/723,000 (0.5%) reported in 2013 programmatic data. Conclusion High TB rates among older adults in TB endemic areas justify consideration of active TB case finding and prevention strategies.